2016
DOI: 10.1051/0004-6361/201526706
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a dense aperture array for radio astronomy

Abstract: EMBRACE@Nançay is a prototype instrument consisting of an array of 4608 densely packed antenna elements creating a fully sampled, unblocked aperture. This technology is proposed for the Square Kilometre Array and has the potential of providing an extremely large field of view making it the ideal survey instrument. We describe the system, calibration procedures, and results from the prototype.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The PAON4 antennas are installed near the EMBRACE prototype (Torchinsky et al 2016), and could therefore be easily connected to the electric mains and Ethernet network. At this place, the ground is particularly loose and in order to avoid having to build expensive and fixed concrete foundations, the antenna structures are slightly flexible with respect to horizontal stability, and are equipped with four legs in a statically undetermined configuration.…”
Section: Reflectors and Feed Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAON4 antennas are installed near the EMBRACE prototype (Torchinsky et al 2016), and could therefore be easily connected to the electric mains and Ethernet network. At this place, the ground is particularly loose and in order to avoid having to build expensive and fixed concrete foundations, the antenna structures are slightly flexible with respect to horizontal stability, and are equipped with four legs in a statically undetermined configuration.…”
Section: Reflectors and Feed Designmentioning
confidence: 99%
“…FFT beam-forming is also possible using a regular grid of antenna, including dishes, as mentioned by (Tegmark & Zaldarriaga 2009). Such a strategy has already been implemented on a modest scale in individual LOFAR stations for the High Band Array, and at ∼ 1 GHz frequencies in EMBRACE (Torchinsky et al 2016). This was the ultimate goal of the SKA mid frequency array with an early demonstrator called 2-PAD (Armstrong et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Various small-scale engineering systems have shown good results [6], and most recently the EMBRACE system has demonstrated that a large-scale aperture array system capable of making competitive astronomical measurements is now within reach [7,8]. What is absolutely clear is that so long as data sampling and processing costs continues to fall, the construction of a scientifically productive large aperture array operating at GHz frequencies becomes more of a question of not if, but when.…”
Section: Seti and Aperture Arraysmentioning
confidence: 99%
“…To experiment with all these concepts, an ongoing case study has been conducted on the Electronic Multi-Beam Radio Astronomy Concept (EMBRACE) radio telescope facility at Nançay Observatory (see Figure 4.a and (Torchinsky et al, 2016)). The objective of the experiment is to evaluate the RFI mitigation strategy in terms of hardware complexity, detection efficiency and additional RFI metadata datarate cost.…”
Section: Fig 2 Spectrummentioning
confidence: 99%
“…EMBRACE is a phased-array radio telescope (Torchinsky et al, 2016). Based on a LOFAR station firmware, it provides a set of 200 kHz digital single polarization waveforms from 2 independent beams.…”
Section: Overviewmentioning
confidence: 99%